Pseudophakic Retinal Detachment: A Narrative Review - Karniela Ayuni Putri; Weni Helvinda; Khalilul Rahman (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Cataract surgery causes changes in intraocular conditions that are a risk factor for retinal detachment. One of the conditions that can occur during cataract surgery is posterior capsule rupture which can increase the risk of pseudophakic retinal detachment (PRD). PRD examination is often obstructed by opacification of the posterior capsule, a reflection of the intraocular lens (IOL), or poor mydriasis. Scleral buckle, pneumatic retinopexy, and primary pars plana vitrectomy, with or without a combination of the scleral buckle, are surgical techniques used in the management of PRD patients. Anatomical and functional postoperative success rates in PRD patients were found to be higher after primary pars plana vitrectomy (PPV) with or without a scleral buckle. This literature review aims to discuss the epidemiology, risk factors, pathogenesis, and management of PRD.